Deficiency of IL-20 receptor subunit A decreases enterovirus A71 lethality in mice by increasing M1 macrophage polarization and cytokine production - Hung, Cheng-Huei; Hsiao, Yi-Ling; Tsai, Yi-Ping; Chang, Ming-Shi; Liu, Ching-Chuan; Wang, Li-Chiu; Chen, Shun-Hua (Frontiers in Immunology, 2026)
IntroductionEnterovirus A71 (EV-A71) can cause fatal disease accompanied by increased cytokines, including IL-10, IL-12, and IFN-γ, which are mutually regulated. IFN-γ is induced to protect mice from EV-A71 infection, but its regulation remains unclear. The IL-10 family cytokines, IL-19, IL-20, and IL-24, which signal through a two-subunit receptor complex containing IL-20 receptor subunit A (IL-20RA), are designated as IL-20RA cytokines. IL-20RA cytokines are known to regulate IFN-γ and IL-10 in vitro. We designed this study to investigate the interaction and role of IL-20RA cytokines in viral infection in vivo, which remain unknown.MethodsPlasma from healthy donors and EV-A71-infected patients was analyzed to detect IL-20RA cytokines. Wild-type (WT) and IL-20RA knockout (IL-20RA-/-) mice, as well as isolated T cells and macrophages, were used for functional studies.ResultsIn plasma samples, IL-19 was detectable in healthy controls, and EV-A71 infection increased IL-19 levels in infected patients. In sera of WT mice, IL-20RA cytokines, but not IL-10, IL-12, or IFN-γ, were detected in mock-infected animals, and EV-A71 infection significantly increased IL-19 and slightly increased IL-20 levels. Compared with WT mice, IL-20RA-/- mice were resistant to EV-A71 infection, with reduced viral loads in peripheral organs, such as the spleen. In sera of infected mice, IL-20RA deficiency sequentially reduced IL-10 levels but increased IL-12 and IFN-γ levels. Abundant T cells expressed IL-10 in splenocytes of infected WT mice, whereas abundant macrophages expressed IL-12 and IFN-γ in splenocytes of infected IL-20RA-/- mice. Notably, IL-20RA deficiency reduced M2 macrophages but increased M1 macrophages in splenocytes of infected mice. In vitro, treatment of leukocytes isolated from WT mice with IL-19 or IL-20, but not IL-24, increased IL-10 production in CD4 T cells and reduced IL-12 production in macrophages.DiscussionEV-A71 infection enhances IL-20RA cytokines, which then increase viral loads and aggravate disease severity in WT mice by elevating the T cell–IL-10–M2 macrophage axis and suppressing the protective M1 macrophage–IL-12–macrophage–IFN-γ axis. This represents a previously unreported mechanism.